Associations among mask wearing behavior and the theory of planned behavior constructs in undergraduate students during and post-mask mandate - Kianna M Arthur; Rachel Smallman; Jessica C Lowe; Yang Ni; Sherecce Fields (Health Psychology Open)
This study sought to examine the predictive utility of the theory of planned behavior (TPB) for mask wearing behavior. Data was collected during the Texas public mask mandate (October 11-November 24, 2020) and post-mandate (March 25-April 29, 2021). University students were recruited through the department’s online subject pool. Participants during the mandate ( N = 579; M = 18.70, SD = 1.17; 60.8% female) and post-mandate ( N = 236; M = 19.15, SD = 1.02; 50% female) completed identical TPB measures and demographic measures. Using structural equation modeling (SEM), attitudes, subjective norms and perceived behavioral control were associated with stronger mask wearing intentions. Intentions were positively associated with mask wearing behavior. Perceived behavioral control also had a direct positive association with wearing a mask in public. These findings suggest that the TPB is successful in predicting mask wearing behavior, which could have implications for prevention programs and public health campaigns.